Stabilization of a Membrane-Associated Amyloid-β Oligomer for Its Validation in Alzheimer's Disease - Serra-Batiste, Montserrat; Tolchard, James; Giusti, Fabrice; Zoonens, Manuela; Carulla, Natàlia (Frontiers in Molecular Biosciences, 2018)
We have recently reported on the preparation of a membrane-associated β-barrel Pore-Forming Aβ42 Oligomer (βPFOAβ42). It corresponds to a stable and homogeneous Aβ42 oligomer that inserts into lipid bilayers as a well-defined pore and adopts a specific structure with characteristics of a β-barrel arrangement. As a follow-up of this work, we aim to establish βPFOAβ42’s relevance in Alzheimer’s disease (AD). However, βPFOAβ42 is formed under dodecyl phosphocholine (DPC) micelle conditions—intended to mimic the hydrophobic environment of membranes—which are dynamic. Consequently, dilution of the βPFOAβ42/DPC complex in a detergent-free buffer leads to dispersion of the DPC molecules from the oligomer surface, leaving the oligomer without the hydrophobic micelle belt that stabilizes it. Since dilution is required for any biological test, transfer of βPFOAβ42 from DPC micelles into another hydrophobic biomimetic membrane environment, that remains associated with βPFOAβ42 even under high dilution conditions, is a requisite for the validation of βPFOAβ42 in AD. Here we describe conditions for exchanging DPC micelles with amphipols (APols), which are amphipathic polymers designed to stabilize membrane proteins in aqueous solutions. APols bind in an irreversible but non-covalent manner to the hydrophobic surface of membrane proteins preserving their structure even under extreme dilution conditions. We tested three types of APols with distinct physicochemical properties and found that βPFOAβ42/DPC complex can only be trapped in non-ionic APols (NAPols). The characterization of the resulting βPFOAβ42/NAPol complex by biochemical tools and structural biology techniques allowed us to establish that the oligomer structure is maintained even under high dilution. Based on these findings, this work constitutes a first step towards the in vivo validation of βPFOAβ42 in AD.